1998
DOI: 10.1136/oem.55.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Are long working hours and shiftwork risk factors for subfecundity? A study among couples from southern Thailand.

Abstract: Objective-To estimate the eVect of long working hours and shift work on time to pregnancy. Methods-Cross sectional samples with retrospective data collection from two 700 bed hospitals at secondary to tertiary care level in Hatyai district, Songkhla Province, Thailand. The study was conducted from March 1995 to November 1995 among 1496 pregnant women attending the antenatal clinics. Subfecundity was defined as time to pregnancy longer than 7.8, 9.5, or 12 months (time to pregnancy was calculated from the date … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 38 publications
(24 reference statements)
1
35
0
3
Order By: Relevance
“…This is in accordance with Irgens et al [41] who reported a tendency toward reduced semen quality among shift workers (OR: 1.46, 95% CI: 0.89-2.40) which may be explained by stress and specific lifestyle factors. Moreover, Tuntiseranee et al estimated the effect of long working hours and shift work on time-to-pregnancy and they found that long working hours constitute a risk factor for subfecundity, but, shift work was not associated with subfecundity in their study [42]. However, Zhu et al examined whether shift work is associated with reduced fecundity as estimated by time-to-pregnancy (TTP).…”
Section: Resultsmentioning
confidence: 99%
“…This is in accordance with Irgens et al [41] who reported a tendency toward reduced semen quality among shift workers (OR: 1.46, 95% CI: 0.89-2.40) which may be explained by stress and specific lifestyle factors. Moreover, Tuntiseranee et al estimated the effect of long working hours and shift work on time-to-pregnancy and they found that long working hours constitute a risk factor for subfecundity, but, shift work was not associated with subfecundity in their study [42]. However, Zhu et al examined whether shift work is associated with reduced fecundity as estimated by time-to-pregnancy (TTP).…”
Section: Resultsmentioning
confidence: 99%
“…A possible negative impact of long work hours on reproduction is subfecundity (defined by the study: time of 7.8 months or longer to pregnancy for couples who plan a pregnancy) 50) . Meta-analysis of six high-quality studies by Mozurkewich et al 51) suggested a weak relationship between long working hours in pregnant women and preterm birth (Odd Ratio = 1.24 with a 95% Confidence Interval of 1.04 to 1.48).…”
Section: Reproductionmentioning
confidence: 99%
“…Long working hour affects the health of employee, make them have no time to take care of their families, especially their children. It may also produce negative effect on husband-wife relationship (Behar, 2001), parent-child relationship (Fursman, 2009), pregnancy planning (Moss, 2009), ease of getting pregnancy (Tuntiseranee et al, 1998) and increase risk or abortion (Hatch et al, 1997). All these factors may interact and decrease pregnancy and decrease birth rate (Young, 2016).…”
Section: The Theoretical Foundation Of the Studymentioning
confidence: 99%